2008
DOI: 10.1152/ajprenal.90254.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acute anal stretch inhibits NMDA-dependent pelvic-urethra reflex potentiation via spinal GABAergic inhibition in anesthetized rats

Abstract: The impact of acute anal stretch on the pelvic-urethra reflex potentiation was examined in urethane-anesthetized rats by recording the external urethra sphincter electromyogram activity evoked by the pelvic afferent stimulation. Test stimulation (1 stimulation/30 s) evoked a baseline reflex activity with a single action potential that was abolished by gallamine (5 mg/kg iv). On the other hand, the repetitive stimulation (1 stimulation/1 s) induced spinal reflex potentiation (SRP) that was attenuated by intrath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the previous study, glutamatergic excitatory transmission was found in the descending limb of the spinobulbospinal micturition reflex pathway [23], and glutamatergic mechanisms play an essential role for micturition in the rat spinal cord [24]. In the pelvic-urethra reflex, N-methyl-d-aspartate-dependent potentiation is inhibited via spinal γ-aminobutyric acidergic (GABAergic) inhibition [25]. Intrathecal injection of α1-adrenoceptor blockers clearly inhibits the micturition reflex in animal models [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, glutamatergic excitatory transmission was found in the descending limb of the spinobulbospinal micturition reflex pathway [23], and glutamatergic mechanisms play an essential role for micturition in the rat spinal cord [24]. In the pelvic-urethra reflex, N-methyl-d-aspartate-dependent potentiation is inhibited via spinal γ-aminobutyric acidergic (GABAergic) inhibition [25]. Intrathecal injection of α1-adrenoceptor blockers clearly inhibits the micturition reflex in animal models [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…2008a,b,c). Our laboratory also demonstrated that cross‐organ sensitization induction is linked to development of viscero‐visceral referred pain, for it is characterized by pathological enhancement of urethra activity, caused by activation of nociceptive afferent fibers arising from abdominal/pelvic viscera (Chen et al. 2007, 2008; Liao et al.…”
mentioning
confidence: 93%
“…Pharmacological investigation revealed that NMDA-dependent calcium ion influx resulted in phosphorylation of the NR2B subunit, which underlies cross-organ sensitization development (Peng et al 2008a,b,c). Our laboratory also demonstrated that cross-organ sensitization induction is linked to development of viscero-visceral referred pain, for it is characterized by pathological enhancement of urethra activity, caused by activation of nociceptive afferent fibers arising from abdominal/pelvic viscera (Chen et al 2007(Chen et al , 2008Liao et al 2007a,b;Peng et al 2008d).…”
mentioning
confidence: 76%